PROXIMATE AND MINERAL COMPOSITION OF FRESHWATER FISHES - Natarajan, M V; Sreenivasan, A (Indian Journal of Fisheries, 2011)
DATA on chemical composition of many of the freshwater fishes of our country is not available and hence an attempt has been made to analyse as many as thirty-six species. The chemical composition of fish varies widely from species to species and season to season. There is also individual variation in the same species. A knowledge of chemical composition is essential in order to compare its value as food with other protein foods. Stansby (1954) has elaborated on the importance of chemical analysis.